P.S. wish you were here - Stine, Megan (HarperEntertainment New York, 2000)
Shares the diaries of twin sisters, one of whom is at boarding school while the other returns home to rejoin her softball team, as they cope with being apart, with a case of plagiarism, and with meeting other people's expectations